2014
DOI: 10.1089/cmb.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for the Nonpathogenic Nonsynonymous Single-Nucleotide Polymorphisms of Acetylcholinesterase in the Treatment of Alzheimer's Disease: A Computational Study

Abstract: Single-nucleotide polymorphisms (SNPs) are implicated in the complexity of understanding the genetics of diseases and their therapeutics. Here we have attempted to determine the impact of nonsynonymous SNPs (nsSNPs) on structure, dynamics, and ligand-binding properties of the human acetylcholinesterase (hAChE) protein, which has been targeted in the treatment of Alzheimer's disease. Of the reported 153 SNPs, 4 nsSNPs, namely, A415G, P104A, V302E, and Y119H, were prioritized to be functionally unfavorable by SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Hence the HPH peptides could bind to the active site to interfere with substrate binding ability to the ee AChE. At the same time, the HPH peptides have the capacity to bind to non‐active sites on the ee AChE protein, which could have led to changes in molecular conformation that distorts the active site molecular arrangement and thus there is reduced substrate binding ability (Saravanaraman et al, ; Sharma, ; Singh et al, ). The results are consistent with a recent report by Zhao et al () who showed that lysine (free amino acid) inhibited ee AChE activity through a mixed‐type mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the HPH peptides could bind to the active site to interfere with substrate binding ability to the ee AChE. At the same time, the HPH peptides have the capacity to bind to non‐active sites on the ee AChE protein, which could have led to changes in molecular conformation that distorts the active site molecular arrangement and thus there is reduced substrate binding ability (Saravanaraman et al, ; Sharma, ; Singh et al, ). The results are consistent with a recent report by Zhao et al () who showed that lysine (free amino acid) inhibited ee AChE activity through a mixed‐type mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…This abberant brain and neurotransmission condition leads to Alzheimer's disease (AD) pathogenesis (Li et al, 2015;Willcox, Scapagnini, & Willcox, 2014) that contributes to increased global morbidity/mortality rate (US Burden of Disease Collaborators, 2013). The high catalytic efficiency (CE) of AChE and the importance of its inhibition in AD management has been an important research focus in the development of various therapeutic agents (Acharya, Dutta, Chaudhury, & De, 2018;Li et al, 2015;Olarewaju et al, 2018;Saravanaraman, Chinnadurai, & Boopathy, 2014;Taslimi & Gulçin, 2018;Yadav & Appukuttan, 2019;Yatesa et al, 2019;Zare-Zardini, Tolueinia, Hashemi, Ebrahimi, & Fesahat, 2013). Several synthetic AChE-inhibitory drugs have been developed for use against neurodegenerative diseases, such as dementia and AD; however, these drugs are associated with severe negative side effects (Ghribia, Ghouilaa, Omrib, Besbesb, & Janneta, 2014;Iannello et al, 2014;Kumar & Chowdhury, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of the reported 153 SNPs, four non-specific SNPs (A415G, P104A, V302E, and Y119H) that were predicted to be functionally unfavorable were found to be structurally stable. However, their conformational alterations were found to interfere with the binding of AChE inhibitors, suggesting it to be a reason for the differential effect of ChEIs in patients with AD [ 78 ]. Similar results were observed in another study conducted in patients with AD who underwent treatment with AChE inhibitors (N=158).…”
Section: Factors Affecting Clinical Response To Cheismentioning
confidence: 99%
“…On the other hand, the studying of radiation enzyme damages is limited . Acetylcholinesterase (AChE) is one of the enzymes which is composed of catalytic triad in the active site consisting of the amino acids, serine (Ser), histidine (His), and glutamic acid (Glu) . AChE can synthesize neurotransmitter acetylcholine (ACh) by the transition of acetyl groups of acetyl CoA .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Acetylcholinesterase (AChE) is one of the enzymes which is composed of catalytic triad in the active site consisting of the amino acids, serine (Ser), histidine (His), and glutamic acid (Glu). [10][11][12] AChE can synthesize neurotransmitter acetylcholine (ACh) by the transition of acetyl groups of acetyl CoA. [13][14][15] The reaction efficiency of AChE is significantly larger than the other enzymes.…”
Section: Introductionmentioning
confidence: 99%